2020
DOI: 10.1292/jvms.20-0245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protocatechuic acid on ameliorating lipid profiles and cardio-protection against coronary artery disease in high fat and fructose diet fed in rats

Abstract: A coronary heart disease leads to increase in obesity and metabolic dysfunction. Protocatechuic acid (PCA), due to its antioxidant, anti-inflammatory, neuro protective activities was found efficient as cardio-protective in coronary heart disease. Our study investigated hypolipidemic and cardioprotective effects of protocatechuic acid in the coronary artery disease induced by high fat and fructose diet (HFD) rat models. A diet rich in fat and fructose was fed to male wistar rats prior to the start of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…On the other hand, concomitant PCA administration with MSG provoked potent hypolipidemic and hypoglycemic activities which agree with recent studies (El-Sonbaty et al 2019, Li et al 2020. PCA showed notable decrease in the activity of pancreatic lipase that is essential for absorption of triglycerides from the gastrointestinal tract (Li et al 2020). Similar results were previously reported in diabetic, and D-galactosamine-exposed rats (Harini &Pugalendi 2010, Radhiga et al 2016.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, concomitant PCA administration with MSG provoked potent hypolipidemic and hypoglycemic activities which agree with recent studies (El-Sonbaty et al 2019, Li et al 2020. PCA showed notable decrease in the activity of pancreatic lipase that is essential for absorption of triglycerides from the gastrointestinal tract (Li et al 2020). Similar results were previously reported in diabetic, and D-galactosamine-exposed rats (Harini &Pugalendi 2010, Radhiga et al 2016.…”
Section: Discussionsupporting
confidence: 91%
“…High blood glucose level possibly attributed to encouragement of hepatic gluconeogenesis as well as low tissue insulin sensitivity (Seiva et al 2012). On the other hand, concomitant PCA administration with MSG provoked potent hypolipidemic and hypoglycemic activities which agree with recent studies (El-Sonbaty et al 2019, Li et al 2020. PCA showed notable decrease in the activity of pancreatic lipase that is essential for absorption of triglycerides from the gastrointestinal tract (Li et al 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…SA chia sprouts exerted the highest reduction in BWG, and this material had the highest TPC content. Our group found that elicitation with SA in chia sprouts increased mainly di‐hydroxybenzoic acid (data not shown) and its most representative isomer, the protocatechuic acid, reduced BWG in rats fed HFFD (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Especially, we expect that the diseases due to compromised H 2 O 2 reduction in human body such as decreased expression of peroxisome can easily be treated with PCA. In addition, PCA’s antioxidant capacity can be linked to anti-inflammatory activity and the phenolic compound can be used to treat inflammation-related diseases such as neurodegenerative diseases ( Kaewmool et al, 2020 ), coronary artery disease ( Li et al, 2020a ), and allergic asthma ( Li et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%